Pragmatic failure in the heterogeneous communication - Ismoilova, Dilorom (Журнал иностранных языков и лингвистики, 2021)
The article discusses the importance of teaching pragmatics in EFL classes. The author highlights the pragmatic failure and its negative consequences in the heterogeneous communication process.